European inflation expectations dynamics - Jirka Slacalek; Ulrich Fritsche; Jonas Dovern; Jörg Döpke (Deutsche Bundesbank, 2005)
This paper investigates the relevance of the sticky information model of Mankiw and Reis (2002) and Carroll (2003) for four major European economies (France, Germany, Italy and the United Kingdom). As opposed to the benchmark rational expectation models, households in the sticky information environment update their expectations sporadically rather than instantaneously owing to the costs of acquiring and processing information. We estimate two alternative parametrizations of the sticky information model which differ in the stationarity assumptions about the underlying series. Using survey data on households? and experts? inflation expectations, we find that the model adequately captures the dynamics of household inflation expectations. Both parametrizations imply comparable speeds of information updating for the European households as was previously found in the US, on average roughly once a year.
Keywords: E31; 330; Inflation; expectations; sticky information; inflation persistence; Inflationserwartung; Schätzung; Deutschland; Frankreich; Italien; Großbritannien; sticky information